The Cultural Relations of Water in Remote South Australian Towns - Ben Wadham; Eileen Willis; Meryl Pearce (Fenomena, 2010)
Water is a natural resource that is becoming increasingly scarce, and declining rainfall forces communities to adapt to living in drought and significantly different environmental and social conditions. In remote residential areas of South Australia, water tends to be the only natural resource used daily, requiring them to pay attention to their relationship with water, access, and adequacy. These are the issues that need consideration. However, lifestyles, identity, sense of belonging, and community have been shaped by the presence of water in daily habits. Water also becomes a social issue, and its management arises in cultural relations. Air adalah sumber alam yang semakin jarang ditemukan, dan penurunan curah hujan menyebabkan masyarakat harus beradaptasi untuk hidup dalam kekeringan, serta kondisi lingkungan dan sosial yang sangat berbeda. Pada perumahan penduduk di Australia Selatan yang terpencil, air cenderung sebagai satu-satunya sumber alam yang dipergunakan sehari-hari sehingga mengharuskan mereka memperhatikan hubungan mereka terhadap air, akses, serta kecukupannya. Inilah hal-hal yang perlu diperhatikan. Akan tetapi, gaya hidup, identitas, rasa memiliki, dan komunitas telah sedemikian terbentuk dengan adanya air dalam kebiasaan setiap orang. Air juga menjadi masalah sosial, dan pengaturannya timbul dalam hubungan budaya.